2012
DOI: 10.1111/j.1651-2227.2012.02744.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in breast milk: relation to serum adiponectin concentration in lactating mothers and their infants

Abstract: The observed correlations between adiponectin in mothers, HM and BF infants may be suggestive for a metabolic link between nurses and infants through milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
6
33
0
2
Order By: Relevance
“…Median levels of adiponectin in our study were substantially lower (by a factor of 2-5) than those reported from women in Italy, Mexico, and the United States (Woo et al 2009;Savino et al 2012). We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994).…”
Section: Discussionsupporting
confidence: 82%
“…Median levels of adiponectin in our study were substantially lower (by a factor of 2-5) than those reported from women in Italy, Mexico, and the United States (Woo et al 2009;Savino et al 2012). We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, maternal serum concentrations of adiponectin are lower if weight and BMI are higher [29,30]. Results associating maternal BMI and adiponectin concentrations in HM are conflicting [25], with several studies showing no associations [11,31,32] and two studies counter-intuitively reporting a positive association [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The complex system of breastfeeding-mediated appetite regulation is attributable to various factors associated with the practice of breastfeeding, such as feeding on demand, but also potentially to a host of appetite regulatory molecules present in HM [4]. These include whey and casein proteins, HM oligosaccharides, and recently discovered in HM appetite regulatory hormones, including the well-documented adipokine leptin, adiponectin, and many others [10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%